An analysis of McMurdo Dry Valleys’ lotic habitats within Antarctica’s protected area network and addressing gaps in biodiversity protection - Anna Wright; Cassandra Brooks; Michael Gooseff; Adrian Howkins; Stephen Chignell (Arctic, Antarctic, and Alpine Research)
The McMurdo Dry Valleys (MDV), Antarctica’s largest ice-free region, hosts unique terrestrial ecosystems, with biodiversity concentrated in the aquatic environments and surrounding soils. Despite being a scientific hub, the creation of the MDV Antarctic Specially Managed Area (ASMA) made significant steps toward protecting the environment from degradation from human usage. However, with sustained human presence within the MDV, increasing human activity across Antarctica, and aquatic ecosystems subject to environmental change, the effectiveness of current protections for biodiversity conservation requires evaluation. This study employs spatial analysis of MDV protected areas, streams, lakes, research camps, and tourist sites to assess the robustness of current protections, identify underprotected areas, and outline steps for future protection. Within the MDV ASMA, five smaller Antarctic Specially Protected Areas (ASPAs) exist. Only two ASPAs contain streams, and only one with a full hydrologic catchment. With roughly 6% of the lotic habitat area protected by ASPAs, the MDV fall short of global goals for freshwater protection. Past successful management of the MDV shows the effectiveness of collaboration and early action, and amongst calls for ASPA network expansion and restructuring, the MDV has the opportunity to be at the forefront again and increase the protection of Antarctic aquatic ecosystems.